2019
DOI: 10.1186/s12199-019-0830-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of pre-sick building syndrome: characteristics of indoor environmental and individual factors

Abstract: Background: With the aim to prevent sick building syndrome and worsening of allergic symptoms, primarily resulting from the indoor environment, the relationships among people's residential environment in recent years, their lifestyle habits, their awareness, and their symptoms were investigated using an online survey. Methods: In the survey, respondents experiencing symptoms specific to sick building syndrome, although they were not diagnosed with sick building syndrome, were categorized in the pre-sick buildi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 39 publications
3
24
0
3
Order By: Relevance
“…More than 50% of the respondent’s homes in this study were positive for one or more dampness indicators. Notably, we found a significant association between dampness index (0–4) values and SBS symptoms, which also supports previous studies [ 1 , 10 , 17 , 26 , 27 ]. Specifically, our stepwise analysis in Table 5 confirmed a persistent and significant association between dampness index (0–4) and all SBS symptoms, thus indicating that dampness is the most common independent indoor variable for SBS.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…More than 50% of the respondent’s homes in this study were positive for one or more dampness indicators. Notably, we found a significant association between dampness index (0–4) values and SBS symptoms, which also supports previous studies [ 1 , 10 , 17 , 26 , 27 ]. Specifically, our stepwise analysis in Table 5 confirmed a persistent and significant association between dampness index (0–4) and all SBS symptoms, thus indicating that dampness is the most common independent indoor variable for SBS.…”
Section: Discussionsupporting
confidence: 93%
“…This indicates that SBS may be experienced in children independent of allergic symptoms. This could be attributed to factors other than allergic diseases, such as indoor environmental pollutants (e.g., dampness, chemicals, and/or microbial factors), which may increase SBS in non-allergic children [1,8,10,11,27]. Further, our stepwise analysis revealed that the presence of any allergies (an independent variable) was associated with mucosal and skin symptoms (Table 5), which also supported previous studies [13,26].…”
Section: Allergies and Sbssupporting
confidence: 88%
See 1 more Smart Citation
“…For example, reducing the concentration of sum of volatile organic compounds (ΣVOCs) in living environments and the odor of specific chemicals can reduce the occurrence of building related symptoms (BRSs) [3,4]. In epidemiological studies, lifestyle changes such as frequent ventilation and cleaning were shown to reduce the occurrence of BRSs, asthma, and other allergic symptoms [5][6][7][8][9]. Very recently, improving the indoor-air environment through ventilation has proven effective against COVID19 infection [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…People spend more than 80% of their time indoors thus securing optimal conditions is crucial to avoid any unfavorable consequences [14]. According to current data, the Sick Building Syndrome (SBS) is connected with a substantial share of modern buildings, public in particular [15]. The syndrome associates several health problems of people who work or live in these areas, such as respiratory illnesses, wheezing, skin or eye irritation and concentration disorders [16,17].…”
Section: Introductionmentioning
confidence: 99%